Insight into the mechanism of selective mono-N-methylation of aniline on Cu1-xZnxFe2O4: a DRIFTS study - Vijayaraj, M.; Murugan, B.; Shubhangi B. Umbarkar; Hegde, S. G.; Gopinath, Chinnakonda S. (Journal of Molecular Catalysis A - Chemical, 2005)
Mechanism of selective mono-N-methylation of aniline with methanol on Cu1-xZn2FeO4 catalysts was investigated in detail. The interaction of reactants (aniline. methanol and methanol: aniline) and possible products (N-methylaniline (NMA), N,N-dimethylaniline (DMA) and o-toluidine (OT)) on catalysts surface was studied by temperature-dependent in situ FTIR spectroscopy. Methanol adsorbs dissociatively over catalysts surface at 373 K as methoxy species and is oxidized to formate species at high temperature through dioxymethylene and/or formaldehyde as a surface intermediate species. On the other hand, adsorption of aniline:methanol mixtures shows that methanol oxidation was completely hindered in the presence of aniline. Aniline adsorbs on the Lewis acid sites at <= 373 K with phenyl ring oriented in a perpendicular manner to the catalyst surfaced however, N-H bond scission occurs above 373 K. A comparison of adsorbed NMA and methanol: am line (3:1) mixture on Cu0.5Zn0.5Fe2O4 shows NMA forms from the reaction mixture at 473 K. However, maximum activity at 573 K in catalytic reaction studies suggests that desorption limits the methylation kinetics. FTIR study displays stable aniline and methyl species on ZnFe2O4 even at 573 K; however. no methyl species is detected on Cr0.95Zn0.05Fe2O4 at 473 K due to methanol reforming reaction and that limits the overall reaction and hence low catalytic activity. It is proposed that methanol is protonated on catalysts surface by the labile H+ due to N-H bond scission. Co-adsorption of acidity probes with aniline and methanol indicates that aniline methylation takes place at single acid-base site. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Aniline; Cu1-xZnxFe2O4; desorption limited; DRIFT; IR; Methanol; N-methylaniline; N-methylation; reaction mechanism

Nature of manganese species in Ce1-xMnxO2-delta solid solutions synthesized by the solution combustion route - Murugan, B.; Ramaswamy, A. V.; Srinivas, D.; Gopinath, Chinnakonda S.; Ramaswamy, V. (Chemistry of Materials, 2005)
A series of manganese-cerium oxide composites with Mn concentrations in the range of 1-20 mol % in ceria was prepared by the solution combustion technique using urea as fuel. The nature, type, and oxidation state of Mn species in ceria were investigated by X-ray diffraction (XRD), diffuse reflectance UV-visible spectroscopy, electron paramagnetic resonance (EPR), X-ray photoelectron spectroscopy, and temperature-programmed reduction techniques. The study reveals that the method of preparation significantly influences the type of manganese species in ceria. Wet-impregnation, coprecipitation, and solid-state synthesis techniques lead to clustered MnOx-like species in the ceria matrix, while the present method of preparation (solution combustion route) yields a highly dispersed form of Mn species. In the reported series of samples, Mn is present mainly in +2 and +3 oxidation states and there is no evidence for the presence of Mn 41 species. Powder X-ray diffraction studies at variable temperatures (298-1323 K) indicate the formation of Ce1-xMnxO2-delta Solid solutions. No separate MnOx-type phase was detected even at 1323 K. EPR studies reveal that the isolated Mn2+ and Mn2+ species are present in at least three different structural locations: species A, Mn ions in ceria-lattice defect sites; species B, Mn ions in framework Ce4+ locations; and species C, Mn ions in interstitial locations and at the surface of ceria. The Mn3+ ions in ceria exhibit a facile reduction and reoxidation behavior when exposed to dry hydrogen and subsequently to air at elevated. temperatures. A highly dispersed state of Mn3+ and Mn2+ in ceria, facile redox behavior, and a synergistic Mn-ceria interaction are some of the unique properties of this material prepared by the solution combustion procedure.

Effect of fuel and its concentration on the nature of Mn in Mn/CeO2 solid solutions prepared by solution combustion synthesis - Murugan, B.; Ramaswamy, A. V.; Srinivas, D.; Gopinath, Chinnakonda S.; Ramaswamy, Veda (Acta Materialia, 2008)
Nano and microcrystalline, Mn/CeO2 solid solutions (5 mol.% Mn) have been prepared by solution combustion synthesis using urea, glycine or polyethylene glycol (PEG) as fuel. The nature of the fuel and its concentration (fuel to metal mole ratio, F/M have a strong influence on the physical and chemical characteristics of the resulting Mn/CeO2 solid solutions. The variations in the physicochemical properties are attributed to differences in (i) the adiabatic/real flame temperature realized with these fuels at different F/M ratios; (ii) the sustenance of the temperature or the quenching effect of the fuel at higher F/M ratios; (iii) combustion or decomposition of the precursors as the main course of the reaction; and (iv) the generation of gaseous products during combustion. Since the addition of the fuel to the initial precursor solution does not change the pH of the medium, the differences in the type of Mn species formed are mainly attributed to the combustion process. (C) 2007 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Combustion synthesis; Mn-ceria; Nanocomposites; X-ray diffraction (XRD); X-ray photoelectron spectroscopy (XPS)